Treatment of Patient with Diabetic Nephropathy using Chinese Prescription Kangen-karyu - Hiratani, Kazuyuki; Shoji, Masahiro; Osanai, Makoto; Zhang, Liye; Park, Chan Hum; Natazuka, Toshiki; Yokozawa, Takako (Archives of Clinical and Medical Case Reports, 2019)
Diabetic nephropathy is among the main causes of end-stage renal disease worldwide. The mainstay of diabetic nephropathy has been the management of hyperglycemia, blood pressure, and proteinuria using hypoglycemic agents, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers. The utilization of traditional Chinese medicine to diabetic nephropathy has received increasing attention due to its wide availability, weak side-effects, and proven therapeutic mechanisms and benefits. In this paper, we report the case of a 54-year-old patient with a 10-year history of diabetes, who showed a marked improvement in diabetic nephropathy on the administration of 7.5 g of Kangen-karyu extract per day. After 6 months, estimated glomerular filtration rate had increased from 95.8 to 104.2 ml/min/1.73 m2. Urinary protein and albumin levels decreased following administration. At that time, the somatic and subjective symptoms had partially disappeared. Herein, we present and discuss the evidence supporting the use and mechanism of Kangen-karyu extract against diabetic nephropathy based on the patient.